Fuzzy logic applications in inland waterway transportation - Bugarski Vladimir; Kulić Filip; Kanović Željko; Bačkalić Todor (Journal on Processing and Energy in Agriculture, 2020)
New applications of a fuzzy expert system (FES) for direct control of traffic lights in the areas of locks and one-way sections on inland waterways are presented. FES implements the knowledge of experts in the field of water transport on a controller. FES-SL (application in ship locks) was created for a single-chamber two-way ship lock. The system decides when the lock process will be performed depending on the current requests and queues. FES-1WS (application in one-way sections) was created for a canal network with sections where one-way vessel traffic is allowed due to the width limitation. The system is applicable for different traffic densities (from 10 to 90 vessels per day) and different lengths of one-way sections (from 2km to 24km).